Human Cultures Through the Scientific Lens: Essays in Evolutionary Cognitive Anthropology - Boyer, Pascal (Open Book Publishers, 2021)
This volume brings together a collection of seven articles previously published by the author, with a new introduction reframing the articles in the context of past and present questions in anthropology, psychology and human evolution. It promotes the perspective of 'integrated' social science, in which social science questions are addressed in a deliberately eclectic manner, combining results and models from evolutionary biology, experimental psychology, economics, anthropology and history. It thus constitutes a welcome contribution to a gradually emerging approach to social science based on E. O. Wilson's concept of 'consilience'.